Advances in intelligent and autonomous aerospace systems - Valasek, John (Progress in astronautics and aeronautics, 2012)
This book provides aerospace researchers and engineers with a discussion of the latest innovative methods and approaches that focus on intelligent and autonomous aerospace systems. The chapters are written by leading researchers in this field, and include ideas, directions, and recent results on intelligent aerospace research issues with a focus on dynamics and control, systems engineering, and aerospace design. The content on uncertainties, modeling of large and highly non-linear complex systems, robustness, and adaptivity is intended to be useful in both the sub-system and the overall system level design and analysis of various aerospace vehicles. A broad spectrum of methods and approaches are presented, including: bio-inspiration; fuzzy logic; genetic algorithms; Q-learning; Markov decision processes; approximate dynamic programming; artificial neural networks; probabilistic maps; multi-agent systems; and Kalman, particle, and confidence filtering. --